Simplified model of cooling/heating load prediction for various air-conditioned room types - Napassawan Khammayom (2020)
© 2019 The purpose of this study is to develop simplified cooling/heating load models for a various air-conditioned room, applying the Buckingham-Pi theorem. The model is used to estimate cooling/heating loads of air-conditioned room at reduced calculation time. An experimental room for cooling load had been set up at Chiang Mai University, Thailand in summer season during March to April in 2018. On the other hand, an experiment room for heating load had been set up at Mie University, Japan during December 2018 to February 2019. Room temperatures were set at 27 °C–25 °C for cooling and 24 °C–21 °C for heating. Collected data, such as room air temperature, room relative humidity, ambient temperature and solar radiation were used to calculate appropriate constants for cooling/heating load model. To validate the accuracy of the simplified model, calculated heating/cooling load from the model was compared to the calculated cooling/heating load from the traditional method. The results demonstrated that the simplified model developed from Buckingham-Pi theorem could estimate the cooling/heating load by low computational complexity with acceptable accuracy, comparing to results from traditional calculation method.